2012
DOI: 10.1051/0004-6361/201118455
|View full text |Cite
|
Sign up to set email alerts
|

GS305+04-26: revisiting the interstellar medium around the Centaurus OB1 stellar association

Abstract: Context. Massive stars deeply modify their surrounding interstellar medium (ISM) via their high throughput of ionizing photons and their strong stellar winds. In this way, they may create large expanding structures of neutral gas. Aims. We study a new large neutral hydrogen (Hi) shell, labelled GS305+04-26, and its relationship with the OB association Cen OB1. Methods. To carry out this study, we have used a multi-wavelength approach. We analyse both Hi line data retrieved from the LeidenArgentina-Bonn (LAB) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 33 publications
1
18
1
1
Order By: Relevance
“…In these new spectroscopic and astrometric studies we found 56 members of Cen OB1 and NGC 4755, while in Corti et al (2012) 54 members of Cen OB1 and NGC 4755 were found, so between both works there are 43 members in common. For this reason the total energy supplied to the interstellar medium by this new group of members of Cen OB1 and NGC 4755 is 17% lower than the energy published in Corti et al (2012).…”
Section: Membershipmentioning
confidence: 62%
See 4 more Smart Citations
“…In these new spectroscopic and astrometric studies we found 56 members of Cen OB1 and NGC 4755, while in Corti et al (2012) 54 members of Cen OB1 and NGC 4755 were found, so between both works there are 43 members in common. For this reason the total energy supplied to the interstellar medium by this new group of members of Cen OB1 and NGC 4755 is 17% lower than the energy published in Corti et al (2012).…”
Section: Membershipmentioning
confidence: 62%
“…For this reason the total energy supplied to the interstellar medium by this new group of members of Cen OB1 and NGC 4755 is 17% lower than the energy published in Corti et al (2012). With the contribution of energy to the Hi shell GS305+04-26 given by the pulsars, it is sufficient to generate this Hi shell, as was stated in Corti et al (2012).…”
Section: Membershipmentioning
confidence: 75%
See 3 more Smart Citations